Effective Use of Textbooks by Early Education Teachers - Marzenna Nowicka (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: Schoolbooks are the basic didactic tool in early childhood education classes. As evidenced by numerous research reports, their content is significantly diversified in terms of quality. However, empirical research providing insight into teachers' experiences of working with school textbooks is lacking. Research Aim: This study examines how teachers influence the use of a school textbook. It looks at their views on daily work with textbooks, the advantages and disadvantages they perceive, and their responses to these observations. Method: Six focus group interviews with 37 early childhood education teachers were conducted. The collected material was subsequently subjected to meaning-oriented content analysis. Results: On the basis of the collected data, it was established that teachers construe textbooks as: predestined fate, a stabilizing factor in the didactic process, a tool for everyday work, a subject-matter expert and a surety of their responsibility for the learning process. The work of educators with the school textbook is characterized by conformity, limited flexibility, adaptation to the range of children's aptitudes, rationalization and, in rare cases, resistance. Conclusions: With respect to working with school textbooks, the agency of teachers manifests itself only as a superficial response to the identified shortcomings, without an autonomous approach to the content as well as tasks and instructions in school textbooks. Such a conclusion may offer grounds for a pedagogical discussion on the limitations and needs of training early education teachers in terms of enhancing their agency while working with a school textbook.